Look Good Today or to Look Good Everyday? - Sowmya Naga Dogiparthi (Dermatology, 2016)
When we introduce ourselves to a stranger, the first thing they notice is our appearance. Skin, Hair and Nails give each one of us an external appearance that one see’s before knowing anything about the person. For both men and women racial Skin types vary from Fitzpatrick Skin Types I-VI; Type I being very Pale White Skin prone to burning all the time and at the end of the spectrum is Type VI skin which never burns, but easily gets tanned and deeply pigmented. The genetic variation in human skin colors is mainly because their melanocytes produce different amount and kinds of melanin. Melanocytes are the pigment producing cells being the product of both of the individual’s biological parents’ genetic makeup. The amount of melanocytes and the type of melanin production within the epidermis determines the skin and hair color of an individual.